Voltage-Gated K+/Na+ Channels and Scorpion Venom Toxins in Cancer - Díaz-García, Alexis; Varela, Diego (Frontiers in Pharmacology, 2020)
Ion channels have recently been recognized as novel therapeutic targets in cancer research since they are overexpressed in different histological tissues, and their activity is linked to proliferation, tumor progression, angiogenesis, metastasis, and apoptosis. Voltage gated-potassium channels (VGKC) are involved in cell proliferation, cancer progression, cell cycle transition, and apoptosis. Moreover, voltage-dependent sodium channels (VGSC) contribute to decreases in extracellular pH, which, in turn, promotes cancer cell migration and invasion. Furthermore, VGSC and VGKC modulate voltage-sensitive Ca2+ channel activity by controlling the membrane potential and regulating Ca2+ influx, which functions as a second messenger in processes related to proliferation, invasion, migration, and metastasis. The subgroup of these types of channels that have shown a high oncogenic potential have become known as “oncochannels”, and the evidence has highlighted them as key potential therapeutic targets. Scorpion venoms contain a high proportion of peptide toxins that act by modulating voltage-gated Na+/K+ channel activity. Increasing scientific data have pointed out that scorpion venoms and their toxins can affect the activity of oncochannels, thus showing their potential for anticancer therapy. In this review, we provide an update of the most relevant voltage-gated Na+\K+ ion channels as cellular targets and discuss the possibility of using scorpion venom and toxins for anticancer therapy.